Oxalate degradation by alkaliphilic biofilms acclimatised to nitrogen-supplemented and nitrogen-deficient conditions - Weerasinghe Mohottige, T.; Cheng, K.; Kaksonen, A.; Sarukkalige, Priyantha Ranjan; Ginige, M. (Wiley, 2018)
Background: Sodium oxalate is a key organic contaminant in alumina industry, which diminishes process yields and product quality. Given that Bayer process liquor is typically deficient in nitrogen (N), there is external supplementation of N in current full‐scale biological treatment processes. This study, for the first time, examines oxalate degradation under N deficient conditions using two parallel biofilm‐reactors, one N‐supplemented and the other under N‐deficient conditions. Oxalate degradation rates and oxygen uptake rates (OUR) were determined at different bulk water dissolved oxygen (DO) set‐points. Results: The results revealed that oxalate removal rates (33–111 mg h‐1 g‐1biomass) linearly correlate with OUR (0–70 mg O2 h‐1 g‐1biomass) in the N‐supplemented reactor. However, in the N‐deficient reactor, a linear increase of oxalate removal was recorded only with DO up to 3 mg L‐1. Surprisingly, anaerobic oxalate removal was evident even in the presence of DO (up to 8 mg L‐1) in both reactors. Further elucidation revealed formate, acetate and methane by‐products during anaerobic oxalate removal in both reactors. Conclusion: This study revealed the feasibility of aerobic oxalate oxidation and fermentation under alkaline and N‐deficient conditions. Further, this study confirms the critical role of DO in aerobic oxalate biodegradation.